Comparative Analysis of V-Shaped Rib Configurations for Enhanced Cooling Performance in Gas Turbine Blades - Kumpanat Chaiphet; Nattadon Pannucharoenwong; Phadungsak Ratanadecho (Science & Technology Asia, 2026)
This study conducts a numerical analysis of six different V-shaped rib configurations installed in a square internal cooling passage (aspect ratio, AR=1:1), representing a typical gas turbine blade cooling channel. Using the RNG 𝑘 −𝜀 turbulence model, simulations were conducted for Re ranging from 5,000 - 30,000 to evaluate heat transfer and flow characteristics through three primary metrics: the Nusselt number (Nu), friction factor ( 𝑓 ), and thermal enhancement factor (TEF). As Re increases, secondary vortices intensify, enhancing mixing and heat transfer. Although continuous V-shaped ribs (Model 1) provide the greatest heat transfer rate, they generate considerable flow resistance. Alternating continuous ribs (Model 2) achieve the highest TEF, particularly at lower Reynolds numbers, by balancing heat transfer improvement with moderate pressure losses. Discontinuous and alternating rib designs (Models 3–6) effectively decrease the pressure drop while sustaining acceptable heat transfer levels. These findings emphasize the importance of rib geometry in controlling turbulence, pressure loss, and thermal performance, offering valuable guidelines for optimizing internal cooling designs in turbine blades.